Biopotency of Salicylic Acid against Oviposition and Feeding Behavior of Pectinophora gossypiella in Cotton - Muhammad Rehan Akhtar; Muhammad Jalal Arif (Biology and Life Sciences Forum, 2023)
Pectinophora gossypiella (Saunders) is a potential threat for the successful cultivation of cotton all over the world. Despite the use of modern management strategies, the damage caused by this pest is increasing. The repeated exposure of this pest to Bacillus thuringenisis (Bt) crops resulted in resistance development, which has threatened the continued success of Bt cotton cultivation. Salicylic acid has been reported to enhance the efficiency of crops. The present study was carried out to determine the effect of salicylic acid on the oviposition (pre-oviposition and post-oviposition time) and feeding behavior (pre-feeding time and post-feeding time) of pink bollworm larvae in two cotton varieties, i.e., CIM-70 and NIAB-78. In the first experiment, leaves and bolls treated with different concentrations of salicylic acid were kept in an oviposition chamber and adults were released in a chamber with a ratio of 5:5 males to females, respectively. The experiment was performed following a Completely Randomized Design (CRD) with three replications and six concentrations of salicylic acid (0, 10, 20, 40, 80, and 160 ppm). In a second complementary experiment, salicylic acid was evaluated against feeding behavior, i.e., larval duration, pre-feeding time, feeding time, post-feeding time, and percentage mortality of pink bollworm. In both experiments, the results revealed that the application of salicylic acid at a maximum concentration was effective against the oviposition and feeding of pink bollworm only in the NIAB-78 cultivar. It is concluded that salicylic acid has the potential to reduce pink bollworm risks, and the present investigation will help researchers as well as farmers plan for the timely sustainable management of pink bollworm.